Intrageneric relationships and description of a new West African species in Gerbilliscus (Rodentia, Muridae, Gerbillinae) - (:unkn) unknown (My University, 2012)
The systematics of the African rodent genus Gerbilliscus is still a matter of debate. At the genus level it has been said to include the related genus Gerbillurus, and at the species level some species still need to be definitely recognized as distinct. To tackle these questions, we gathered and analyzed mitochondrial (cytochrome b) and nuclear (BRCA1) gene sequences in a number of specimens representing ten species of Gerbilliscus and three species of Gerbillurus. Phylogenetic reconstructions confirm that Gerbillurus should be considered a synonym of Gerbilliscus. They also clearly show that species diversity in this group is spatially organized, with geographically well-defined species groups covering major areas of sub-Saharan Africa, namely Southern, Eastern and Western Africa. In the latter area, a well-supported genetic lineage appears to correspond to a hitherto overlooked species, also characterized by a distinctive karyotype. This species is characterized by an overall large size, a relatively long tail, a distinct karyotype, and represents a well-differentiated genetic cluster. It ranges from Benin to Guinea in Sudano-Guinean forest-savanna mosaic habitats, where it can be sympatric with the congeneric species G. kempi and G. guineae. Detailed body and skull morphological and biometrical analyses performed on samples of the West African species, including type specimens described in this region, suggest that this species may correspond to G. kempi. If confirmed, this would imply that what is currently named G. kempi would deserve another species name, the most likely of which would be G. giffardi.
Keywords: African Research